The five year lie eaudiobook - Bowen, Sarina (HarperAudio, 2024)
"I devoured this book in one day, and I guarantee you will too."—Julie Clark, New York Times bestselling author of The Last Flight and The Lies I Tell "An expertly woven story of love, revenge, and murder. In a world where so many books feel so similar — this was a refreshingly unique read and an addictive blend of love and mystery that I couldn't put down. This is storytelling at its finest and I can't recommend this book enough."—AR Torre, New York Times bestselling author of Every Last Secret Bestselling romance author Sarina Bowen's debut thriller, about one woman's search for the truth after receiving a text from her deceased ex. She thought it was love. Then he vanished. On an ordinary Monday morning, Ariel Cafferty's phone buzzes with a disturbing text message. Something's happened. I need to see you. Meet me under the candelabra tree ASAP. The words would be jarring from anyone, but the sender is the only man she ever loved. And it's been several years since she learned he died. Seeing Drew's name pop up is heart-stopping. Ariel's gut says it can't be real. But she goes to the tree anyway. She has to. Nobody shows. But the text upends everything she thought she knew about the day he left her. The more questions she asks, the more sinister the answers get. Only two things are clear: everything she was told five years ago is wrong, and someone is still lying to her. The truth has to be out there somewhere. To safeguard herself—and her son—she'll have to find it before it finds her. And with it, the answer to what became of Drew. For fans of Laura Dave and Julie Clark, but with a heart-stopping romance that only Sarina Bowen can execute, The Five Year Lie is a spine-tingling thriller that will have you guessing until the very end.